Burnout among nurses, midwives, and physicians in maternity care exposed to traumatic childbirth events - Robinson, Keisha A.; Atlas, Robert O.; Storr, Carla L.; Gaitens, Joanna M.; Blanchard, May.; Ogbolu, Yolanda (2024)
Nurses, midwives, attending physicians, and resident physicians in training at five hospitals with maternity services in the Baltimore, Maryland area participated in a survey about burnout and exposure to traumatic childbirth events. Maternity clinicians experience burnout at similar rates to those in other specialties. Development of evidence-based strategies that prioritize the wellbeing of clinicians is crucial.
Keywords: Nurses -- Job stress; Midwives -- Job stress; Physicians -- Job stress; Burn out psychology